Malaysia's healthcare expenditure: ARDL bound test / Noormahayu Mohd Nasir ...[et al.] - Mohd Nasir, Noormahayu; Nasir, Zarul Azhar; Abdullah Fahami, Norasyikin; Ahmad Kusairee, Muhammad Adidinizar Zia; Ramli, Khalijah (Universiti Teknologi MARA, 2021)
This study aims to analyse the relationships between income level, education expenditure, inflation, and ageing population towards health expenditure in Malaysia over the period of 1997 until 2017. This study employs Auto regressive Distributed-Lag (ARDL) Bound test in determining the long-run empirical relationships between all independent variables and healthcare expenditures in Malaysia. The findings show the existence of long run co integration between healthcare expenditure inflation, income level, and the government's education expenditure. The results confirmed that all independent variables have positive long run relationships, except the ageing population that displays a negative relationship in influencing healthcare expenditure in Malaysia. The regression result of GDPP shows income elasticity value of 0.690, reflecting the necessity of healthcare expenditure. The outcome of the paper hopes to provide insights on the importance of healthcare expenditure for the development of this country, especially on its economic fronts.